Effects of elevated CO2 levels on eggs and larvae of a North Pacific flatfish. (6th April 2015) - Hurst, Thomas P.; Laurel, Benjamin J.; Mathis, Jeremy T.; Tobosa, Lauren R.
Abstract: The Bering Sea and Gulf of Alaska support a number of commercially important flatfish fisheries. These high latitude ecosystems are predicted to be most immediately impacted by ongoing ocean acidification, but the range of responses by commercial fishery species has yet to be fully explored. In this study, we examined the growth responses of northern rock sole ( Lepidopsetta polyxystra ) eggs and larvae across a range of CO2 levels (ambient to 1500 µatm) to evaluate the potential sensitivity to ocean acidification. Laboratory-spawned eggs and larvae were reared at 8°C in a flow-through culture system in which CO2 levels were maintained via computer-controlled injection of CO2 into a seawater conditioning tank. Overall, we observed only minor effects of elevated CO2 level on sizes of northern rock sole larvae. Size at hatch differed among offspring from four different females, but there was no significant effect of CO2 level on egg survival or size at hatch. In three separate larval growth trials, there was little effect of CO2 level on growth rates through the first 28 d post-hatch (DPH). However, in the one trial extended to 60 DPH, fish reared at the highest CO2 level had lower condition factors after 28 DPH, suggesting that larvae undergoing metamorphosis may be more sensitive to environmental hypercapnia than earlier pre-flexion stages. These results suggest that while early life stages of northern rock sole are less sensitive to ocean acidification than previously examined flatfish, they may be more sensitive to elevated CO2 levels than a previously studied gadid with a similar geographic range.